Use of Copernicus data for developing a geoportal to support agricultural management monitoring in Poland - Markowska Anna; Paradowski Karol (Polish Cartographical Review)
This article focuses on mapping agricultural productivity, which can be assessed using vegetation and environmental satellite indices (e.g., NDVI, NDWI). It highlights the main agricultural risks in Poland, namely spring frosts and agricultural droughts. The significance of employing remote sensing indicators to create maps supporting agricultural management at national and voivodeship levels is emphasised. The article demonstrates how such maps can be developed using selected satellite-derived indices for agricultural monitoring across different administrative levels. Furthermore, it discusses access to satellite data from the European Copernicus Programme, including land cover, vegetation condition, and weather data (e.g., ERA5). The paper presents the results of a project undertaken by the Institute of Geodesy and Cartography in Poland (IGiK), which developed a geoportal designed for institutions involved in supporting agricultural development in Poland – KOWR (National Support Centre for Agriculture; in Polish: Krajowy Ośrodek Wsparcia Rolnictwa) and ARMA (Agency for Restructuring and Modernisation of Agriculture; in Polish: Agencja Restrukturyzacji i Modernizacji Rolnictwa).